Wadi Shuʿaib, Jordanien: Das Wadi Shuʿaib Archaeological Survey Project – Archäologische Forschungen zwischen Jordantal und transjordanischem Hochland - Ahrens, Alexander (e-Forschungsberichte des DAI, 2023)
The Wadi Shuʿaib Archaeological Survey Project (WSAS) was initiated in2016. During the fall of 2016, a first preliminary survey campaign was conductedin the region of the Wadi Shuʿaib, stretching from the town of as-Saltin the northwest to the Jordan Valley (Shuna South) in the southwest of CentralJordan. During the first survey campaign, altogether fourteen archaeologicalsites were recorded, most of which were hitherto unknown, while otherswere already known to the scholarly community, but never recorded and documentedthoroughly. The aim of the survey in future campaigns is to recordall archaeological sites in this micro region connecting the fertile Jordan Valleywith the Transjordanian Highlands.